MOTION ESTIMATION IN BRAIN TOPOGRAPHIC MAPS - GOPALAKRISHNAN, GOWRI (Universiti Teknologi Petronas, 2011)
The objective of brain mapping is to advance knowledge in understanding the brain functions with its respective structures. Current technologies and advances in brain imaging technique using EEG (electroencephalogram) allows estimation of network connection which represents activity that occur in different structures of human brain. As the EEG procedure is >imple and harmless, it is widely used to study the brain behavior and cognitive processes such iS memory, language, emotions, sensation and alertness. In past study, ten healthy subjects (five female and five male) undergo an experiment consists of 200 trials. These trials include two >timulus consist of X and 0 which appears randomly. Subjects required to respond to X and ignore 0. Signals gained from these events evaluated as topographical properties of brain aetwork. Note that, only segment of interest will be plotted on topographic maps. In present research, these topographic maps will be used to study the behavior of the brain signals due to presence of stimulus. Motion estimation is an interesting analysis of tracking movement of signals around brain region. Currently, no proper motion estimation technology is available for this purpose. Development of motion estimation system allows us to observe and study movements of brain signals. In this project, I've applied Full Search Algorithm on brain topographic. Movement of signals detected based on general matching criteria which will be further discussed in the literature review.